Dreamland's: know about science electricity - Talwar, L.M (Dreamland Publications New Delhi, 1995)
Dreamland's: Know About Science - Electricity introduces young readers to the basics of electricity, explaining concepts like electric current, circuits, and how electricity powers everyday devices. With colorful illustrations and simple explanations, the book makes learning about electricity engaging and accessible. It often includes fun experiments and activities that encourage hands-on exploration.